Pharmacological corrections of the mutant hERG channels by posaconazole. (25th February 2021) - Luo, Chaodi; Zheng, Xinglong; Li, Jing; Zhang, Yongjian; Shi, Tao; Yan, Yang; Han, Dan
Abstract: Properties of mutant human ether‐à‐go‐go‐related gene (hERG) channels can be modified by some antibiotics. However, the pharmacological effects of posaconazole on cardiomyocyte hERG channels remain unclear. Whole‐cell patch clamping, western blotting and laser confocal scanning microscopy were used to evaluate the effects of posaconazole on wild‐type (WT)‐, A561V‐ and L539 fs/47‐hERG channels expressed in human embryonic kidney (HEK) 293 cells. In electrophysiological experiments, HEK 293 cells were transiently co‐transfected with equal amounts of WT‐hERG, WT+A561 V‐hERG and WT+L539 fs/47‐hERG plasmids to mimic a heterozygous genotype. Posaconazole (30 μM) increased tail currents in cells expressing WT‐hERG, WT+A561 V‐hERG and WT+L539 fs/47‐hERG by 82.65%, 147.72% and 134.73%, respectively, compared to controls. Posaconazole increased hERG protein expression in cells expressing WT‐hERG, WT+A561 V‐hERG and WT+L539 fs/47‐hERG compared to controls condition as well as their trafficking to the cell membrane. To our knowledge, this is the first study to show that antifungal agent posaconazole rescues the mutant A561 V‐hERG and L539 fs/47‐hERG channels by altering the gating kinetics, enhancing the expression and trafficking of hERG channels. The results demonstrate that posaconazole could be a promising candidate for the prevention and treatment of long QT syndrome and other arrhythmia‐related diseases.